2010
DOI: 10.1289/ehp.0901827
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Evidence on the Health Effects of Perfluorooctanoic Acid (PFOA)

Abstract: Objective and sourcesWe reviewed the epidemiologic literature for PFOA.Data synthesisPerfluorooctanoic acid (PFOA) does not occur naturally but is present in the serum of most residents of industrialized countries (U.S. median, 4 ng/mL). Drinking water is the primary route of exposure in some populations, but exposure sources are not well understood. PFOA has been used to manufacture such products as Gore-Tex and Teflon. PFOA does not break down in the environment; the human half-life is estimated at about 3 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
370
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(382 citation statements)
references
References 71 publications
(183 reference statements)
9
370
2
1
Order By: Relevance
“…First, it was impossible to establish a causal inference due to the cross-sectional nature of this study (Grimes and Schulz, 2002). Second, both PFAAs and serum lipids might be jointly affected by some other attributes, substances or mechanisms that caused the associations between them (Steenland et al, 2010). Third, after the information of age, gender and BMI was adjusted, it might be still possible that residual confounding persisted due to unknown factors (Fisher et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…First, it was impossible to establish a causal inference due to the cross-sectional nature of this study (Grimes and Schulz, 2002). Second, both PFAAs and serum lipids might be jointly affected by some other attributes, substances or mechanisms that caused the associations between them (Steenland et al, 2010). Third, after the information of age, gender and BMI was adjusted, it might be still possible that residual confounding persisted due to unknown factors (Fisher et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…For example, as one of the most concerned PFCs, PFOS is present in the blood of general population at a level of about 20 ppb and an estimated half-life of nearly 5.4 years (Calafat et al 2007;Olsen et al 2007). Because of the characteristics of wide distribution and high stability, there has been a great concern as to PFCs' potential harmful effects on human health (Steenland et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…1,7) Epidemiologic studies have shown that PFOA exposure is positively associated with increased serum cholesterol and uric acid levels. 8) Moreover, recent studies have indicated that PFOA influences the risk of obesity, as an obesogen, in mice and humans. 9,10) Obesogens are defined functionally as chemicals that promote obesity by increasing the number of fat cells or the storage of fat into existing fat cells.…”
mentioning
confidence: 99%